MONITORING ESSENTIAL SOIL NUTRIENT BASE ON INTERNET OF THINGS ON DIPTEROCARPUS LITTORALIS PLANT - Ahmad Sony Alfathani; Dwi Rahmasari Fatmawati; Gema Wahyu Fadhilah; Khuma Iroh Nur Azizah (OISAA, 2020)
Dipterocarpus littoralis known locally as pelahlar, is a producer of endemic commercial wood in Nusakambangan. Pelahlar habitat that is isolated in one island and a narrow genetic distribution causes the risk of extinction of this species is increasing. The effort to conserve rare flora can be done by monitoring and observation the balance of essential nutrients at the site of growth. So we need a system that is able to monitor the balance of essential nutrients and pH in the soil to support the growth of rare flora based on the Internet of Things (IoT). This system consists of a sensor station and a central gate station that is connected based on a star network. scheduling of sending data from the sensor station to the gate station is determined from the results of competition between sensor stations based on the backoff of each sensor station. through this scheme an increase in throughput and collision values is based on the number of sensor stations. From our proposed scheme, it is found that the more sensor stations that compete, the smaller the value of the throughput of the system.